Psikoedukasi untuk Meningkatkan Kualitas Hidup Lansia dengan Hipertensi - Jessica Medly Salinding; Nikmah Sofia Afiati (PT. Giat Konseling Nusantara, 2026)
Elderly individuals with hypertension often experience a decline in quality of life due to physical limitations, psychological changes, and reduced social interaction. This condition highlights the need for interventions that address not only medical aspects but also psychological and social dimensions. This community service aimed to improve the quality of life of elderly individuals through psychoeducational intervention within a group-based hypertension management program at a primary healthcare center. The study employed a one group pretest-posttest design with elderly participants. Data were collected through observation, semi-structured interviews, and focus group discussion (FGD). The intervention consisted of several sessions covering physical and mental health education and coping strategies training such as mindful breathing. The results indicated an improvement in participants’ knowledge and understanding of health management, as well as positive changes in psychological and social aspects. The Wilcoxon test showed a significance value of 0.026 (p < 0.05), indicating a significant difference before and after the intervention. It can be concluded that psychoeducation in hypertension management programs is effective in improving the quality of life of elderly individuals through enhanced healthy lifestyle awareness, stress management, and social support.